Pengaruh Metode Bercerita terhadap Peningkatan Kosakata Bahasa Indonesia di RA DZIKRURRAHMAN - Rahmawati, Reni; Perdana, Putri; Pengestina, Ratna (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of the storytelling method in improving early childhood vocabulary acquisition at RA DZIKRURRAHMAN. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles involving planning, implementation, observation, and reflection stages. The subjects were children aged 4-6 years, divided into two groups: an experimental group that received storytelling-based learning and a control group that underwent conventional learning. Data were collected through pre-tests and post-tests to measure vocabulary development before and after the intervention, as well as observations and teacher interviews to understand children's responses to the storytelling method. The results indicate that storytelling significantly enhances children's vocabulary acquisition compared to conventional methods. Children in the experimental group were more engaged in communication, demonstrated a better understanding of new vocabulary, and showed greater enthusiasm during the learning process. Supporting factors for the success of this method include teachers' active involvement in creating an interactive learning environment and the use of engaging visual media. Thus, storytelling can be an effective strategy for improving early childhood vocabulary acquisition.